2011
DOI: 10.1590/s0101-32892011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficácia docente, satisfação e disposição para continuar na docência por professores de educação física

Abstract: Este estudo objetivou identificar e analisar a autoeficácia docente (AED) de professores de educação física e sua relação com nível de satisfação pessoal e de disposição em continuar na atividade de ensino. Participaram 220 professores de escolas públicas e privadas da região de Campinas e do Vale do Paraíba, SP. Foi utilizado uma escala de autoeficácia docente e um questionário de caracterização. A AED foi elevada, sendo que a Eficácia do manejo da classe mostrou-se significativamente inferior quando os profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
23

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
1
2
0
23
Order By: Relevance
“…A study by Ramos et al 17 on the perception of TSE of 78 university students in their third and fourth years of a Physical Education degree at a public university in Santa Catarina state, similarly found elevated levels of TSE. Using the same scale as the cited studies, Iaochite et al 6 found similar results with 220 postgraduate teachers. The results obtained with the use of this scale in different Brazilian universities and regions point to similar results, regardless of the type of institution surveyed (public or private).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A study by Ramos et al 17 on the perception of TSE of 78 university students in their third and fourth years of a Physical Education degree at a public university in Santa Catarina state, similarly found elevated levels of TSE. Using the same scale as the cited studies, Iaochite et al 6 found similar results with 220 postgraduate teachers. The results obtained with the use of this scale in different Brazilian universities and regions point to similar results, regardless of the type of institution surveyed (public or private).…”
Section: Discussionsupporting
confidence: 59%
“…The relationship between TSE beliefs and career satisfaction and engagement 6 , the development of a professional identity 7 , and the enjoyment of the profession 8 , have driven scientific production in the area of professional teacher training. The current challenges have been to identify relationships between TSE and elements that can influence and/or be influenced by TSE beliefs, such as personal characteristics, previous experiences, and contextual variables in which students are incorporated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta autonomia pode proteger o professor de experiências de trabalho tensas justamente porque são essas crenças que farão a diferença na forma como a pessoa pensa, sente e age. Desse modo, um dos aspectos fundamentais deste conceito são as expectativas de autoeficácia, pois são estas que determinam quando, quanto e por quanto tempo é necessário o esforço que será empregado nas ações, diante de obstáculos e de experiências frustrantes Iaochite, Azzi, Polydoro, & Winterstein, 2011;Olaz, 2009;Schwarzer & Hallum, 2008).…”
Section: Percepção De Fontes De Apoiounclassified
“…Experiências vicárias estão relacionadas a situações que envolvem a observação de modelos, conhecida como aprendizagem por observação. Ela pode ser útil quando o indivíduo tem pouca ou nenhuma experiência com a tarefa em questão(IAOCHITE et al, 2011; COSTA FILHO e IAOCHITE, 2015).…”
unclassified